An Analysis of Reading Comprehension Questions in the “Bahasa Inggris Tingkat Lanjut” Textbook for Eleventh-Grade Students - Salsabila, Salsabila; Fitrawati, Fitrawati (Universitas Negeri Padang, 2025)
The purpose of this study is to analyze the forms and levels of reading comprehension questions found in the “Bahasa Inggris Tingkat Lanjut” textbook for eleventh-grade students. This textbook is used in elective English classes under the Merdeka Curriculum in Indonesia. The study used a descriptive quantitative method to classify the forms of questions using Day and Park’s (2005) framework and to identify their comprehension levels based on Barrett’s Taxonomy. This textbook contained 68 reading comprehension questions in total. The findings show that WH-questions are dominant in this textbook (56%), followed by multiple-choice (20%), true/false (15%), yes/no (6%), and alternative questions (3%). In terms of comprehension levels, 47% of the questions are at literal comprehension, 28% inferential, 13% evaluation, and 12% appreciation. No questions are found in the reorganization level. Reeves’ ideal percentage of 40% lower-level, 40% medium-level, and 20% higher-level is not achieved by the distribution of these questions. Students may face difficulty because this textbook contains more lower-level questions, lack of medium-level questions, but a little above higher-level questions. This textbook needs to provide a more evenly distributed variety of questions to help students improve their reading comprehension skills.